Education on Medication Use During Ramadhan at Kowel Community Health Center, Pamekasan - Ach. Faruk Alrosyidi; Ika Oktaviana Dewi; Imam Wahyudi; Sofyan Fadiyanto; Hanafi Hanafi; Anisatul Mafruhah; Alief Putriana Rahman; Naili Uswatun Hasanah; Nanang Setiawan; Risky Mezi Muria (Jurnal Pengabdian Masyarakat Al-Fatimah, 2025)
This study aims to provide optimal education about drug use during the month of Ramadan at the Kowel Community Health Center, Pamekasan. The methods used include direct outreach to the community using a face-to-face concept, distribution of educational materials, and interactive question and answer sessions. The results of the activity show an increase in public knowledge regarding the correct and safe way to use medication during fasting. In conclusion, this education is effective in increasing public awareness of the importance of understanding the use of drugs when fasting. Recommendations for similar activities in the future are to intensify outreach through various media and involve more parties, including health workers and community leaders, to achieve a wider and more sustainable impact